Biologic therapies versus surgical management for aspirin-exacerbated respiratory disease: A review of preliminary data, efficacy, and cost - Workman, Alan D.; Bleier, Benjamin S. (World Journal of Otorhinolaryngology-Head and Neck Surgery, 2020)
Aspirin-exacerbated respiratory disease (AERD) patients with CRSwNP suffer from reduced quality of life, reduced economic productivity, and higher risk of depression and sleep dysfunction. These patients often require frequent medical and surgical therapy, including functional endoscopic sinus surgery for recalcitrant disease. Given this severity, anti-type 2 biologic treatments are being investigated for use in this subgroup of patients with CRSwNP, including Omalizumab and Dupilumab. Preliminary data suggests that SNOT-22 related quality of life improvements following treatment with biologics are comparable to the current standard of care in the short term, but there is a lack of long-term data and standardized regimen that makes direct comparison difficult. Biologic therapies additionally require continuous use to avoid recurrence, and currently cost many times more than existing medical or surgical therapies.